Network Meta-Analysis of the Effects of Different Types of Traditional Chinese Exercises on Pulmonary Function, Endurance Capacity and Quality of Life in Patients With COPD - Li, Lingling; Huang, Hailiang; Song, Jiao; Yu, Ying; Jia, Yuqi; Wang, Yajie; Dang, Xiaowen; Huang, Lei; Liu, Xinyue (Frontiers in Medicine, 2022)
Abstract Background: In recent years, Chinese and international studies have reported that traditional Chinese exercises (TCEs) have good therapeutic effects on pulmonary function, endurance capacity, and quality of life in patients with chronic obstructive pulmonary disease (COPD). However, only a few studies have reported the differences in the efficacy of different TCEs in the treatment of COPD. Objective: The objective of this study is to compare the effects of five TCEs on patients with COPD, including Taijiquan (TJQ), Baduanjin (BDJ), Liuzijue (LZJ), Wuqinxi (WQX), and Yijinjing (YJJ). Methods: All randomized controlled trials (RCTs) of TCEs for patients with COPD were searched in PubMed, Web of Science, Cochrane Library, Excerpt Medica Database (EMBASE), China National Knowledge Infrastructure (CNKI), China Biology Medicine database (CBM), China Scientific Journal Database (VIP), and Wanfang database. The search period was from the establishment of each database to August 16, 2021. The quality of the included studies was assessed according to the Cochrane handbook of systematic review, and the network meta-analysis was conducted with R 4.0.2 (Ross Ihaka, Auckland, New Zealand) and ADDIS 1.16.8 (Gert vsn Valkenhoef, Groningen, Netherlands). The effect size was evaluated using the mean difference (MD) and 95% confidence interval (CI). Results: A total of 53 RCTs involving 3924 patients were included. The network meta-analysis results showed that WQX was the most effective in improving FEV1/FVC% score and 6-MWT score. The difference was statistically significant (MD = 8.62, 95% CI 4.46 to 13.04, P < 0.05), (MD = 74.29, 95% CI 47.67 to 102.24, P < 0.05). However, YJJ was the most effective in reducing the CAT score, and the difference was statistically significant (MD = -8.38, 95% CI -13.24 to -3.28, P < 0.05). Conclusion: The existing evidence shows that WQX has advantages over other TCEs in improving pulmonary function and endurance capacity in patients with COPD, while YJJ has advantages in improving the quality of life. Although TCEs show no significant adverse effects, more large-scale, double-blind, and high-quality RCTs are needed in the future to verify the findings of this study.